A comprehensive analysis of the principles and conditions governance in public-private partnerships - Natalia Sklyaruk (Cхід, 2014)
Public-private partnership is one of the most effective forms of cooperation between public authorities and local self-government with the business in order to solve an important social and economic problems of the municipalities. International practice of interaction between government and the private sector shows that the realization of such projects allows to improve the quality and efficiency of public services, contributes to the modernization and development of socially important infrastructure facilities, stimulate the development of business activity.